Promising indicators for the effectively targeting the poor in Myanmar - Tauseef, Salauddin; Headey, Derek D.; Masias, Ian (2023)
Presentation prepared for MAPSA Learning Series session held on 10 February, 2023. Salauddin Tauseef and Derek Headey (both IFPRI) presented, and Ian Masias (IFPRI) moderated.